Extreme Electrical Storm in Acute Inferior ST‑Elevation Myocardial Infarction Successfully Terminated by Dual Sequential Defibrillation: A Case Report - Somayeh Mirbagheri; Kheironnesa Hajizadeh Ahrami (Case Reports in Clinical Practice, 2026)
Electrical storm and refractory ventricular fibrillation (VF) are rare but catastrophic complications of acute myocardial infarction (AMI) and are associated with high mortality despite adherence to advanced cardiac life support protocols. We report a 48-year-old man with a history of ischemic heart disease, percutaneous coronary intervention, and hypertension who presented with severe exertion-induced chest pain and was diagnosed with acute inferior ST-elevation myocardial infarction. During monitoring, he developed recurrent malignant ventricular arrhythmias progressing to refractory VF despite repeated biphasic defibrillation and antiarrhythmic therapy. Sequential defibrillation with 200-J shocks was performed with procedural sedation and analgesia before each attempt, with a cumulative delivered energy of approximately 4000 J. Intravenous amiodarone, lidocaine, and magnesium sulfate were administered, and thrombolytic therapy with reteplase was initiated. Persistent VF ultimately required dual sequential defibrillation, which successfully restored a stable sinus rhythm. The patient was transferred for urgent coronary angiography and was discharged three days later in stable clinical condition. This case highlights the potential role of dual sequential defibrillation as a rescue strategy in refractory ventricular fibrillation complicating acute myocardial infarction.